1991
DOI: 10.1111/j.1365-2141.1991.tb04427.x
|View full text |Cite
|
Sign up to set email alerts
|

Late onset immune pancytopenia following bone marrow transplantation

Abstract: A 17-year-old boy developed autoimmune pancytopenia in the absence of chronic graft-versus-host disease 170 d after allogeneic bone marrow transplantation (BMT) from his HLA identical brother. The anaemia and thrombocytopenia responded to conventional immunosuppressive treatment, but the neutropenia was refractory to this and to splenectomy and subsequent removal of splenic remnant. Following total lymphoid irradiation the neutrophil count rose to low normal levels but thrombocytopenia and anaemia secondary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Autoimmune haemolytic anaemia (AIHA) has been reported anecdotally following allogeneic marrow transplantation, primarily in patients transplanted with T cell-depleted (TCD) grafts. [3][4][5] In two large retrospective studies the incidence of AIHA after allogeneic bone marrow transplants was estimated at 3%. 6,7 Both series demonstrated that response to conventional treatment was disappointing and a significant proportion of the patients subsequently died from complications related to AIHA or its treatment.…”
Section: Recipientmentioning
confidence: 99%
“…Autoimmune haemolytic anaemia (AIHA) has been reported anecdotally following allogeneic marrow transplantation, primarily in patients transplanted with T cell-depleted (TCD) grafts. [3][4][5] In two large retrospective studies the incidence of AIHA after allogeneic bone marrow transplants was estimated at 3%. 6,7 Both series demonstrated that response to conventional treatment was disappointing and a significant proportion of the patients subsequently died from complications related to AIHA or its treatment.…”
Section: Recipientmentioning
confidence: 99%
“…20 Although rare, autoimmune pancytopenia has also recently been described in two patients undergoing total lymphoid irradiation (TLI) due to failure to respond to conventional immunosuppressive therapy and splenectomy. 21,22 Patient B only responded to the high-dose dexamethasone which was initiated for the cerebral edema at the peak of her thrombocytopenia during her intracerebral bleed. Although TLI was not used in our patients due to the rapid deterioration in patient A and the rapid sustained response to high-dose steroid in patient B, its early use would be worth considering if conventional measures fail to achieve a prompt response.…”
Section: Discussionmentioning
confidence: 99%
“…Admission platelet count was 7 × 10 9 /l, Hb was 9.9 g/dl and WCC was 4.4 × 10 9 /l. Coagulation studies were normal with international normalised ratio (INR) 1.2 (0.9-1.1) and activated partial thromboplastin time (APTT) 35s (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Cultures of blood and urine, in particular, viral cultures and antigen for adenovirus from stools were negative.…”
mentioning
confidence: 99%
“…[2][3][4] The incidence of autoimmune haemolytic anaemia in patients who have been allografted in two series was 3.1% 5 and 5% 6 although this may be an underestimate as mild haemolysis may go undetected. This incidence is much higher than Both cold-type and warm-type antibodies have been reported.…”
mentioning
confidence: 91%